Al-Mubadarat Al-Riyfia: an Islamic finance product for the underserved segment and the third sector of the economy / Adamu Ahmed Wudil and Rislanudeen Muhammad - Wudil, Adamu Ahmed; Muhammad, Rislanudeen (Universiti Teknologi MARA Selangor, 2023)
This paper presents al-Mubadarat al-Riyfia, an innovative Islamic financing product designed to serve the marginalised segment and the third sector of the economy. This paper aims to address the disparity in Islamic finance by emphasising inclusiveness and collective economic well-being. Al-Mubadarat al-Riyfia adopts a group-based approach and focuses primarily on the real business sector, aligning with the principles of value-based intermediation (VBI) in Islamic financing. The primary objective is to provide sustainable financial services to households at low income levels, serving financial needs that often fall within the range of approximately RM500 to RM1000 (approximately US$125-250). The initiative seeks to reach an estimated 40 million households worldwide. This initiative not only addresses the pressing issue of financial inclusion but also contributes significantly to the evolution of Islamic finance. It represents a pioneering effort to integrate underserved populations into the economic mainstream while upholding Islamic finance principles. The study's unique contribution lies in its potential to reshape the landscape of Islamic finance, foster shared prosperity, and provide a model for sustainable development.